2010
DOI: 10.1189/jlb.1209822
|View full text |Cite
|
Sign up to set email alerts
|

Functional overlap but differential expression of CSF-1 and IL-34 in their CSF-1 receptor-mediated regulation of myeloid cells

Abstract: CSF-1 is broadly expressed and regulates macrophage and osteoclast development. The action and expression of IL-34, a novel CSF-1R ligand, were investigated in the mouse. As expected, huIL-34 stimulated macrophage proliferation via the huCSF-1R, equivalently to huCSF-1, but was much less active at stimulating mouse macrophage proliferation than huCSF-1. Like muCSF-1, muIL-34 and a muIL-34 isoform lacking Q81 stimulated mouse macrophage proliferation, CSF-1R tyrosine phosphorylation, and signaling and synergize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
320
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(349 citation statements)
references
References 47 publications
24
320
0
1
Order By: Relevance
“…23,34 Recruitment and differentiation of myeloid cells in tumors are complex processes regulated by multiple pathways, which may lead to differential responses to CSF-1R inhibition. 10,[41][42][43] Several studies have shown that CSF-1/CSF-1R signaling blockade using antibodies or small molecule inhibitors directed against CSF-1R promotes tumor regression, yet the exact mechanism by which this happens is unknown. While some studies have shown that CSF-1R inhibition reduces the number of TAM/myeloid cells, 16,18,23 others have shown that CSF-1R blockade favorably reprograms TAM/myeloid responses without reducing their numbers.…”
Section: Discussionmentioning
confidence: 99%
“…23,34 Recruitment and differentiation of myeloid cells in tumors are complex processes regulated by multiple pathways, which may lead to differential responses to CSF-1R inhibition. 10,[41][42][43] Several studies have shown that CSF-1/CSF-1R signaling blockade using antibodies or small molecule inhibitors directed against CSF-1R promotes tumor regression, yet the exact mechanism by which this happens is unknown. While some studies have shown that CSF-1R inhibition reduces the number of TAM/myeloid cells, 16,18,23 others have shown that CSF-1R blockade favorably reprograms TAM/myeloid responses without reducing their numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and when expressed in vivo under the control of the CSF-1 promoter, the biological activities of homodimeric glycoprotein interleukin-34 (IL-34) resemble those of the secreted glycoprotein isoform of CSF-1 (Wei et al 2010). Although there are significant differences in their signaling through the CSF-1R (Chihara et al 2010), it is primarily the differential expression of IL-34 and CSF-1 (Wei et al 2010;Greter et al 2012;Nandi et al 2012;Wang et al 2012) that results in their differential spatiotemporal regulation through the CSF-1R in vivo (Wei et al 2010;Nandi et al 2012). The transmembrane and proteoglycan CSF-1 isoforms act locally (Wiktor-Jedrzejczak et al 1991;Sundquist et al 1995;Van Nguyen and Pollard 2002;Dai et al 2004;Nandi et al 2006).…”
Section: Csf-1r Expressionmentioning
confidence: 99%
“…In contrast, IL-34 is not detectable in the circulation of healthy individuals (Hwang et al 2012;Tian et al 2013) and thus IL-34 actions are likely to be restricted to the local microenvironments in which they are expressed. Through their different spatiotemporal expression, the two ligands play complementary roles in regulating the development, maintenance, and activity of specific macrophage populations, Langerhans cells, neuronal progenitors (Wei et al 2010;Greter et al 2012;Nandi et al 2012;Wang et al 2012), as well as osteoclasts (Dai et al 2002) and Paneth cells (Huynh et al 2009) and the regulation of cells of the female reproductive tract (Wei et al 2010). Because all of the CSF-1 deficiency phenotypes are also shared with CSF-1R-deficient mice (Dai et al 2002), the CSF-1R appears to be the only receptor for CSF-1, whereas IL-34 has recently been shown to act via an additional receptor, receptortype protein tyrosine phosphatase-z (PTP-z) (Nandi et al 2013).…”
Section: Csf-1r Expressionmentioning
confidence: 99%
“…TAMs TANs Cells/g of tumor ×10 6 Cells/g of tumor ×10 6 Cells/g of tumor ×10 6 Cells/g of tumor ×10 6 Cells/g of lung ×10 6 Cells/g of lung ×10 6 Cells/g of lung ×10 6 Cells/g of lung the more clinically relevant models using immunocompetent mice, anti-CSF-1R has been reported to reduce primary tumor growth (52), and reduce spontaneous metastasis in an osteosarcoma model (51). In the transgenic MMTV-PyMT mouse, studies targeting CSF-1R signaling showed contrasting results.…”
Section: Neutrophils Macrophagesmentioning
confidence: 99%
“…Interleukin-34 (IL34) is a second ligand for CSF-1R; it controls the development of specific macrophage lineages, such as microglia and Langerhans cells (5). IL34 and CSF-1 have distinct expression patterns (6).…”
Section: Introductionmentioning
confidence: 99%